Graphical modeling and simulation of discrete-event systems with CD++Builder. (January 2013) - Bonaventura, Matías; Wainer, Gabriel A; Castro, Rodrigo
We introduce CD++Builder, an open-source environment that aims at providing easy-to-use graphical modeling tools to simplify the construction of models and the execution of simulations of complex Discrete Event System Specification (DEVS) models. The architecture and implementation of CD++Builder focuses on providing simple definition and reuse of components, offering easy extensibility to support new features. CD++Builder includes graphical editors for DEVS-coupled models, DEVS-Graphs and C++ atomic models; it provides code templates that are synchronized with their graphical versions, and it greatly simplifies the software installation and update procedures. We show how this environment can be used to build and simulate DEVS models, and we compare the process with previous versions and other simulation tools, showing that CD++Builder can improve model development by creating DEVS models in a completely assisted manner, including advanced graphical interfaces.